Science and technology development strategy period 2011 - 2020: The key tasks - Khai, Nghiem Vu (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
This paper presents the requirements set forth for the development and implementation of the science and technology (S&T) development strategy for 2011 - 2020 issued in conjunction with Decision 418/QD-TTg dated 11/04/2012 by Prime Minister. One of the requirements for the formulation and promulgation of the strategy was that it must clearly identify tasks and requirements for this S&T development strategic document, avoid duplication of content and format with other types of document such as resolution, program, project… In the strategy elaboration process, the strategy drafting Committee chaired by Ministry of S&T had studied a number of relevant documents on S&T development of other countries such as Japan, China, South Korea, Thailand … Strategies of some countries do not actually aim at setting specific objectives but mainly focus on the analysis of actual situations, the national development goals in order to from there set specific objectives that should be achieved by S&T. It could be said that such documents inclined only towards perceptions, leadership/directive philosophy rather than action plans. Therefore, one of the requirements set forth for this strategy was to express firstly principles, orientations for S&T development and secondly, set out specific targets, tasks and measures for the strategy implementation. For the latter, it should include 3 key items, namely: 1) Radical and comprehensive reform in respect of S&T organization, management and operation mechanism, investment policies and financial mechanism for S&T; 2) Building national S&T capacity including the construction of a system of S&T, and 3) Promote applied research; link scientific research and technology tasks with socio-economic development tasks at national, regional and local level. Code: 13112901 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">